Traumatic Collet-Sicard Syndrome with Associated VIIth and VIIIth Cranial Nerve Palsy: Time for a New Nomenclature - Acharya, Abhijit; Senapati, Satya Bhusan; Panigrahi, Souvagya; Deo, Rama Chandra; Mahapatra, AK (Indian Journal of Neurosurgery, 2023)
Collet-Sicard syndrome (CSS) is a rare condition associated with the involvement of cranial nerve (CN) IX to XII due to lesions involving the jugular foramen and hypoglossal canal. The most common causes are found to be tumors (primary or metastatic), trauma, vascular lesions, inflammatory processes, and iatrogenic complications. Primary intracranial tumors are an extremely rare cause of CSS. However, CSS associated with both CN VII and VIII palsy has been not yet described in English literature. We are presenting a rare case of a 32-year-old man who met with a road traffic accident while riding a bike that resulted in traumatic left-sided involvement of CNs from VII, VIII, IX, X, XI, and XII. The syndromes associated with CSS are mostly jugular foramen syndromes that have been tabulated. The association of CSS with facial palsy is quite rare. So much CN involvement in a traumatic case has so far not been reported in the Medical literature yet and thus, this becomes one of the first cases reported worldwide.
Keywords: Collet-Sicard syndrome; Cranial nerve palsies; facial palsy; magnetic resonance imaging; trauma